The Effect of Bangun-Bangun Leaf Juice on Hemoglobin Levels for Postpartum Mother in The Working Area of Puskesmas Talun Kenas - Ginting, Desideria Yosepha; Purba, Anita Sri Gandaria; Syara, Arfah May; Ginting, Suriani (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2024)
During the puerperium, anemia can occurs in mothers who had lower than nor-mal hemoblobin levels. This condition could caused iron loss, onterfere with the lactatio process, anda cause the uterus to fail to contract because not enough blood enters oxygen to the uterus. The strongest factor causing post partum ane-mia was blood loss during delivery, both moderate and large. Events that cause the mother to lose moderate to large amounts of blood, nameli interventions dur-ing labor such as episiotomy, delivery using a vacuum; third or fourth degree perineal laceration; and caesarean section. The provision of non-drug therapy that can be given to increase hemoglobin levels was to provide iron containing nutrients. The research aim to determine the effect of bangun-bangun leaf juice on hemoglobin levels for postpartum mother in the Working area of Puskesmas Talun Kenas. This research was a type of quantitative research that is quasi-experiment. The population of this study is all postpartummothers in the work area of Puskesmas Talun Kenas. The samples obtained were 25 people with accidental sampling technique. The statistical test used was the paired sample t test, with a 95% confidence level (? = 0,05). The results of this study indicate that there is an effect of bangun-bangun leaf juice on hemoglobin levels in postpartum mothersin the working area of Puskesmas Talun Kenas (p vaue 0,000). So it was expected that the health center could informed the mother about the benefits of bangun-bangun leaf juice in increasing maternal hemoglobin levels during the postpartum period which can informed during antenatal care visits or during home visits for postpartum mother.